Mendelian Inheritance of propranolol responsive hypertension in an Extended Ghanaian family - Addy, J.H. (Ghana Medical Journal, 1990)
Two clear groups, namely hypertensives and 1I0mlOlellsives were identified when several members of 3 generations of an extended Ghanaian family were investigated clinically and historically. Two sets and large numbers of offspring from polygamous marriages ill the family facilitated Mendelian genetic analysis. The first marriage of the female hypertensive prepositus to a normotensive produced two Sons; one was hypertensive the other II0t. Her second marriage to a hypertensive produced six offspring all hypertensive. The hypertensive Son from the prepositus’s first marriage married two normotensive women; the first had six normotensives while the second had one hypertensive and two normotensives; offspring. Two of the female offspring of the prepositus’s second marriage married normotensive men and had several offspring half of whom were hypertensive. 17lis pedigree pattern could be explained 011 Mendelian genetic theory by postulating a pair of alleles, name (H) and (N) genes. On this hypothesis the genotype of hypertension is HH, while that of normotension is NH or NN. This makes H a recessive gene. The marriage between hypertensives (HH) and heterozygous carriers (NH) resulted in hypertensive offspring, giving the false impression that the hypertensive gene was dominant At 30 years of age. hypertensive genotypes developed measurable high blood pressure which was consistently reducible with the B-blocker anti-renin propranolol. An abnormality in the renin-angiotensin system was postulated as tire probable biochemical basis of this inherited Hypertension
Journal Article